204 - EFFECT OF SWIMMING EXERCISE ON SPONGY BONE IN THE OVARIECTOMIZED RATS (Fiep Bulletin - online, 2011)
Introduction The Ovariectomy is characterized by the removal of the ovaries and induces early menopause. Objective evaluate whether the swimming exercise may be indicated for the prevention and control of osteoporosis. Methodology 20 Wistar rats were separated by groups: sedentary control (S), trained control (T), ovariectomized sedentary (OS) and trained ovariectomized (TO). The rats of group T were submitted to swimming exercise, with a load of 5% of body weight for 8 weeks. The induction of menopause, 5 weeks before the start of the experiment was performed by ovariectomy. After the training period the middle third of the femur was collected, fixed and prepared for ultrastructural analysis. Results morphological analysis of spongy bone shows that when compared to T, the bones of the TO and S groups showed a marked decrease in the thickness and the amount of trabecular, while in group S spongy bone was completely absent. In sedentary animals, the interior of the bone has not spongy bone unlike the trained rats. This found the bones of rats trained us to believe that resistance is increased, since in them, can be disposed of with greater efficiency, the forces of tension, compression and torsion to which the bone is subjected during the daily activities. Conclusion swimming promotes the maintenance of bone architecture and can be recommended for prevention of fractures in individuals with osteoporosis.
Keywords: bone; ovariectomy; osteoporosis